Dissimilatory Nitrate Reduction to Ammonium (DNRA) and nrfA Gene in Crop Soils: A Meta‐Analysis of Cropland Management Effects - Qiannan Yang; Hu Li; Lingxuan Gong; Xiaolei Zhang; Lili Wang (GCB Bioenergy)
ABSTRACT Dissimilatory nitrate reduction to ammonium (DNRA) process is an important factor in the removal and retention of nitrogen (N) in cropland soil. However, the effects of cropland management on DNRA rate and nrfA gene abundance are poorly understood on a global scale. A global synthesis based on 29 published papers and 158 observations was conducted to examine the effects of cropland management (including biochar, manure, straw amendment and N fertilization) and identified the controlling factors affecting the DNRA process. We found biochar amendment enhanced DNRA rate by 85%, while manure and straw amendment enhanced DNRA rate by 442% and 160%. Both biochar and straw amendment significantly increased nrfA gene abundance. Biochar significantly increased DNRA rate and nrfA gene abundance in acidic soils in cool climate zones. Manure application increased DNRA rate when N input was low and in coarse‐textured Regosols. Similar to biochar and manure amendment, low N application rate under straw amendment increased DNRA rate in acidic and coarse‐textured soils. The nrfA gene abundance was increased in cool climate and clay loam‐textured soils. Management effects were improved in the long term (> 10 years) experiments. Pearson correlation indicated the crucial roles of alkaline, cool environments and available N in controlling DNRA processes following biochar and straw amendment. Our results also showed the vital roles of alkaline, humid environments and available N controlling the DNRA process under manure amendment and N fertilization. Our study further highlights management practices could enhance N retention through DNRA processes and therefore lower N loss from cropland soil.